2013
DOI: 10.3389/fnhum.2013.00427
|View full text |Cite
|
Sign up to set email alerts
|

Training-induced behavioral and brain plasticity in inhibitory control

Abstract: Deficits in inhibitory control, the ability to suppress ongoing or planned motor or cognitive processes, contribute to many psychiatric and neurological disorders. The rehabilitation of inhibition-related disorders may therefore benefit from neuroplasticity-based training protocols aiming at normalizing inhibitory control proficiency and the underlying brain networks. Current literature on training-induced behavioral and brain plasticity in inhibitory control suggests that improvements may follow either from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
97
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 109 publications
(113 citation statements)
references
References 91 publications
7
97
1
Order By: Relevance
“…Our finding for training-induced decrease in response times (RTs) to Go trials with no change in inhibition trials accuracy replicates the patterns of IC behavioral improvements found in previous studies on Go/NoGo training (Benikos et al 2013;Chavan et al 2015; though see Manuel et al (2010) or Enge et al (2014) for partial speed-accuracy trade-offs and Spierer et al (2013) for a review).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our finding for training-induced decrease in response times (RTs) to Go trials with no change in inhibition trials accuracy replicates the patterns of IC behavioral improvements found in previous studies on Go/NoGo training (Benikos et al 2013;Chavan et al 2015; though see Manuel et al (2010) or Enge et al (2014) for partial speed-accuracy trade-offs and Spierer et al (2013) for a review).…”
Section: Discussionsupporting
confidence: 88%
“…The controlled engagement of frontal inhibitory areas is then bypassed and inhibition speeded up (Manuel et al 2010;Spierer et al 2013). In such training conditions, IC becomes directly triggered by the Stop stimuli via the brain areas implementing stimulus-response (S-R) mapping rules (e.g., parietal cortices 100 ms after the onset of NoGo stimuli in Manuel et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent work suggests that response inhibition can become 'automatic', triggered by the retrieval of previously acquired associations between stimuli and stopping (Spierer, Chavan, & Manuel, 2013;Verbruggen, Best, Bowditch, Stevens, & McLaren, 2014;Verbruggen & Logan, 2008a). In the present study, we examined whether automatic response inhibition is also impaired in individuals with alcoholism.…”
Section: Introductionmentioning
confidence: 92%
“…For example, in an ADHD sample, pharmacological interventions such as methylphenidate improved SST performances (Devito et al 2009). Cognitive training presented mixed results (Koster et al 2017;Maraver et al 2016;Spierer et al 2013). Noninvasive brain stimulation proved to be a useful tool in improving inhibition-based performances (Jacobson et al 2011;Kwon and Kwon 2013).…”
Section: Introductionmentioning
confidence: 99%